TREND OF CODE MIXING RESEARCHES IN SINTA – INDEXED JOURNALS ACROSS INDONESIA - Amirudin Latif; Yasmika Baihaqi; Resfina Melita (English Education Study Program, 2024)
This research describes a study of trends in code-mixing studies in Indonesia during 2015 – 2022 to provide space for further researchers who wish to research code-mixing. By using articles from SINTA-indexed journals, this study aims to find (1) how much code mixing research is in 2015 – 2022, (2) at what level of SINTA code mixing research be found, (3) what types of code mixing are there? Most used in code mixing research, (4) what are the subjects of code mixing research used from 2015 – 2022, (5) what are the data sources used in code mixing research, and (6) what are examples of code sentence mixing of any code mixing research.Qualitative descriptive is the method used in this study. The instrument of this research is documentation, where all the articles that have been found are then downloaded and analysed using the content analysis method. From the use of these data analysis methods and techniques, the research found that there were ten articles on code-mixing from 2015 – 2022. The ten articles came from journals at SINTA levels 2, 3, 4, and 5. The most common type of code-mixing mainly used is word insertion. Subjects, objects, and data sources in code mixing research are divided into two categories: public figures on social media and students. An example of a sentence in code mixing research is